Integrating Primary Health Care and WASH Indicators for Spatial Prioritization of Diarrhoeal Disease Risk in Rural Eastern Indonesia - Muthmainnah; Galuh Mega Kurnia; Yuliana Purnama Sari Min; Dede Nasrullah; Nurul Indah Qariati (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: The objective of this study is to map the distribution of diarrhoeal disease and identify priority sub-districts for targeted prevention in Manggarai District through integration of diarrhoea incidence rate and WASH indicators. The integration of these indicators into a spatial risk framework provides a practical basis for strengthening diarrhoea prevention at the primary care level. Methods: This study employed a descriptive quantitative approach with spatial mapping using Quantum Geographic Information System (QGIS) application. Data of diarrhoea incidence rate and poor WASH indicators (access to improved sanitation, clean water coverage, and handwashing with clean water behavior) from 12 sub-districts from Manggarai Health Profile 2023 and Manggarai Health Office Report 2023 were used. The sub-districts were classified into low, moderate, and high-risk priority level using scoring system and equal interval classification method. Results: West Cibal, North Rahong, and Cibal were classified into high-priority sub-districts characterized by high diarrhoea incidence rate (?4.12 cases per classification range) and poor WASH indicators. Conversely, Langke Rembong, North Satar Mese, and Wae Ri’i exhibited low diarrhoea incidence rate with optimal WASH coverage. Anomalies were found in Lelak, where high diarrhoea incidence persisted despite good WASH access, indicating possible hidden risk factors. Conclusion: The observed spatial patterns showed that inadequate water and sanitation infrastructure, combined with poor hygiene practices, are key drivers of diarrhoeal transmission. The coexistence of high disease burden and weak WASH conditions highlights inequalities in primary health care and environmental service provisioin. By integrating epidemiological, environmental, and behavioral data, this study provides a spatial framework to support targeted diarrhoea prevention and strengthen primary health care planning in resource-limited areas.